Biodistribution of locally or systemically transplantedosteoblast-like cells. Issue 3 (March 2014) - Okabe, Y. T.; Kondo, T.; Mishima, K.; Hayase, Y.; Kato, K.; Mizuno, M.; Ishiguro, N.; Kitoh, H.
Abstract : Objectives: In order to ensure safety of the cell-based therapy for bone regeneration, we examined in vivo biodistribution of locally or systemically transplanted osteoblast-like cells generated from bone marrow (BM) derived mononuclear cells. Methods: BM cells obtained from a total of 13 Sprague-Dawley (SD) green fluorescent protein transgenic (GFP-Tg) rats were culture-expanded in an osteogenic differentiation medium for three weeks. Osteoblast-like cells were then locally transplanted with collagen scaffolds to the rat model of segmental bone defect. Donor cells were also intravenously infused to the normal Sprague-Dawley (SD) rats for systemic biodistribution. The flow cytometric and histological analyses were performed for cellular tracking after transplantation. Results: Locally transplanted donor cells remained within the vicinity of the transplantation site without migrating to other organs. Systemically administered large amounts of osteoblast-like cells were cleared from various organ tissues within three days of transplantation and did not show any adverse effects in the transplanted rats. Conclusions: We demonstrated a precise assessment of donor cell biodistribution that further augments prospective utility of regenerative cell therapy. Cite this article: Bone Joint Res 2014;3:76–81.